Review of Anko Itosu. The Man. The Master. The Myth. Biography of a Legend, by Thomas Feldmann - Eduardo Gonzalez de la Fuente (Universidad de León, 2022)
This review considers the book Anko Itosu. The Man. The Master. The Myth. Biography of a Legend, published in 2021 by Thomas Feldmann. The volume is a thorough biographical study of Anko Itosu (1831-1915), Okinawan born and essential figure to interpret initial developments of karate history during the 20th century. Approximately two decades before this indigenous martial art was to be popularized in mainland Japan by Funakoshi Gichin (1868-1957) and Mabuni Kenwa (1889-1952), and officially recognized by the Dainippon Butokukai [Greater Japan Martial Arts Virtue Society] (1933), Itosu consolidated important technical and discursive changes for karate. This novel way to practice and describe karate, still molding the perception of the art today, had the intention, among others, to further support its inclusion in the school system of Okinawa. Using a huge amount of written and oral sources, historical documents, and scholarly studies on Okinawa, this text offers a vivid picture of Itosu's life. In a manner unusual among the publications on the topic, the text not only explores the early days of modern karate through the existential vicissitudes of the master, but even more importantly it does so against the background of how the cultural, social, and political life was articulated in Okinawa at the time. Such a remarkable effort bears a value that should not go unnoticed among martial arts researchers and the interested reader alike.